Ferroelectric polarization and pyroelectric activity of functionalized P(VDF-TrFE) thin film lead free nanocomposites - Mahdi, Rahman Ismael; Gan, Wee Chen; Abd Majid, Wan Haliza; Mukri, Nurul Izzah; Furukawa, Takeo (Elsevier, 2018)
The ferroelectric, pyroelectric, and dielectric properties of 0–3 nanocomposite systems of ferroelectric (Bi0.5Na0.5)TiO3-(Bi0.5K0.5)TiO3-BaTiO3 ceramics with a vinylidene fluoride/trifluoethylene copolymer were investigated. It was observed that the interface effect between the polymer matrix and nanofiller improves the polarization response in nanocomposite. As a result, significant enhancements in remnant polarization of 130 mC/m2 and pyroelectric sensitivity of 90 μC/m2K are achieved compared to 85 mC/m2 and 26 μC/m2K for pure polymer matrix. Full ferroelectric polarization reversal in the nanocomposite system was supported by a displacement (D) – electric field (E) hysteresis loop and evidence of pyroelectric activity. This finding suggests that the local field plays an important key in facilitating the poling procedure. Therefore, the functional electrical properties of the nanocomposites can be significantly enhanced by controlling the permittivity and conductivity of the inorganic ferroelectric ceramic nanofiller to match the required parameters. Microscopic features of the ferroelectric polarization are also discussed in terms of a two-step switching process. The approach developed her open the way of rational design and assembly of lead free nanocomposite as flexible, light and high performance smart materials, satisfying various requirements for emerging applications.